Effect of different soil types and plant densities on growth dynamic and yield of sweet corn (Zea mays L.) in Peninsular Malaysia - Saiin, Sebrina Shahniza; Ismail, Mohd Firdaus; Ismail, Roslan; Abdul Razak, Sabrina (Sciencedomain International, 2023)
Aims: Soils and plant densities are two of the major factors affecting sweet corn growth and yield. Although many worldwide studies were done to evaluate the effect of these factors on sweet corn, it is still necessary to do more study in this area because environmental factors will give significant effect to growth and yield of sweet corn. The objective of this study is to assess yield optimization through different plant densities for different type of soils for sweet corn (Zea mays L.) cultivation.